Nuclear energy: Russia’s international treaties with other EEU members - Glikman, Olga Vladimirovna; Nazarova, Aziza Ulugbekovna; Filippova, Alina Valeryevna; Minenkova, Ekaterina Gennadyevna (SHS web of conferences, 2021)
The purpose of the study is to identify trends and compare the scope of multilateral and bilateral international legal regulation of relations between Russia and other Eurasian Economic Union members in the field of peaceful use of nuclear power (energy). The methodological basis of the research consists of general scientific and special legal methods. The application of these methods made it possible to subject the current national legislation in the field of nuclear energy to in-depth comparative legal analysis and to identify the prospects for its modernization. The result of the study was the absence of special provisions in the Treaty on the Eurasian Economic Union aimed at integration in the nuclear energy sector and the formation of a common nuclear energy market of the Eurasian Economic Union. The study’s novelty lies in the authors’ approach to the allocation and comparison of the scope and subject matter of existing international treaties of Russia with other Eurasian Economic Union members, regulating cooperation in the peaceful use of nuclear energy, which are not included in the Eurasian Economic Union law. According to the authors, despite the prospects and trends of forming the Eurasian Economic Union nuclear law noted by experts, Russia’s bilateral international agreements with other Eurasian Economic Union members will continue to play a special role in regulating relations in the nuclear energy sector.